COVID-19 in an Urban World - United Nations Executive Office of the Secretary-General (EOSG) (2020)
The remarkable growth of cities in recent decades has intensified a number of humanity’s most pressing challenges. It has also presented many of our greatest opportunities to protect people, prosperity and planet. COVID-19 (coronavirus) has laid bare – and indeed heightened – both these challenges and these opportunities. With an estimated 90 percent of all reported COVID-19 cases, urban areas have become the epicentre of the pandemic. In the near term, for many cities, the COVID-19 health crisis has expanded to a crisis of urban access, urban equity, urban finance, safety, joblessness, public services, infrastructure and transport, all of which are dis-proportionally affecting the most vulnerable in society.